EFFECT OF STORAGE TEMPERATURES ON THE QUALITY OF PINK PERCH SURIMI - M, Ramesh; FAZAL AA; CHANDRASEKHAR TC (Innovare Journal of Food Sciences, 2013)
ABSTRACT A detailed investigation on microbiological, biochemical and organoleptic quality changes in frozen surimi of pink perch (Nemipterus japonicus) stored at ambient (25Â±5Â°C), refrigerated (5Â±3 Â°C) and at frozen temperatures (-10Â±2 Â°C), was carried out. Bacterial count, trimethylamine and total volatile nitrogen values increased with storage time while, organoleptic score decreased. Nutrient contents and gel strength of surimi decreased while, moisture and whiteness increased with storage period. Results indicated that at ambient temperature, frozen surimi can be stored only for about 8 hrs, while at refrigerator temperature up to 5 days and at frozen temperature up to 60 days. Â Â Keywords: Pink pearch, minced meat, surimi, frozen storage. Â